Investigation of DNA topoisomerase I as an autoantigen at the thyroid cancer - Sidorik, L.L.; Rybkinska, T.A.; Vigontina, O.G.; Vudmaska, M.I.; Naidenov, V.G.; Pogribnyi, P.V.; Lisovskii, I.L.; Schvachko, L.P.; Bronstein, I.; Lyzogubov, V.V.; Prihod`ko, E.A.; Usenko, V.S.; et al. (Біополімери і клітина, 2001)
The data concerning DNA-Topoisomerase I (Topo-I) from human placenta as an autoantigen at the thyroid cancer are presented. A new effective scheme of the Topo-I purification using the High-Trap columns is described, as well as the enzyme physico-chemical properties and its immunoreactivity in the ELJSA and immunoblotting. It was shown that 46 % of the sera from patients suffering the thyroid cancer were immunoreactive against Topo-I, 36 % of autoantibodies from thyroid cancer patients sera recognized sequential determinants on the Topo-I molecule. The highest levels of immunoreacivity were observed in the sera of thyroid cancer patients accompanied by autoimmune thyroiditis. We suggest a possible linkage between the autoimmune processes and malignization of the thyroid gland cells. Представлены данные по изучению ДНК-топоизомеразы I (Топо 1), выделенной из плаценты человека, как аутоантигена при раке щитовидной железы. Описана новая эффективная схема очистки Топо I с применением High-Trap-колонок, фико-химические свойства фермента и его иммунореактивность, определенная в реакции ELISA и иммуноблоттинге. Показано, что Топо I-положительными оказались 46 % сывороток пациентов с раком щитовидной железы; из них 36 % содержали аутоантитела против Топо 1, распознающие антигенные детерминанты секвенционного типа. Отмечено, что наиболее иммунореактивными были сыворотки пациентов с раком щитовидной железы и сопутствующим аутоиммунным тиреоидитом. Высказано предположение о возможной связи аутоиммунных процессов со злокачественной трансформацией клеток щитовидной железы. Представлено дані з вивчення ДНК-топоізомерази І (Топо І), виділеної з плаценти людини, як аутоантигена при раку щитовидної залози. Описано нову еффективну схему очищення Топо І з використанням High-Trap-колонок, фізико-хімічні властивості ферменту і його імунореактивність, визначену в реакції EUSA та імуноблотингом. Показано, що Топо I-позитивними виявилися 46 % сироваток пацієнтів з раком щитовидної залози; з них 36 % містили аутоантитіла проти Топо І, які розпізнавали антигенні детермінанти секвенційного типу. Відмічено, що найбільш імунореактивними були сироватки пацієнтів з раком щитовидної залози і супутнім аутоімунним тиреоїдитом. Зроблено припущення щодо можливого зв'язку аутоімунних процесів із злоякісною трансформацією клітин щитовидної залози.